An analysis of the effects on Irish hospital care of the supply of care inside and outside the hospital - Brendan Walsh; Maev-Ann Wren; Samantha Smith; Sean Lyons; James Eighan; Edgar Morgenroth (The Economic and Social Research Institute (ESRI), 2019)
New ESRI research, funded by the Health Research Board, finds that older people are discharged from hospital more quickly in areas with more home care and residential care services.
Keywords: 330